Kasus Langka Karsinoma Sarcomatoid Kandung kemih dan Batu Kandung kemih pada pria berusia 58 tahun : Lapran Kasus - Vincent, Vincent; Mikha, Mikha; Alpendri, Aries (Fakultas Kedokteran Universitas Trisakti, 2023)
BACKGROUND: Sarcomatoid bladder carcinoma is scarcely found, with most cases of bladder carcinoma due to bladder stone as a risk factor consisting of squamous cell carcinoma. Only 221 cases were reported between 1973 and 2004 of sarcomatoid bladder cancer. Therefore, this case report brings out sarcomatoid bladder carcinoma and its clinical relevance. CASE DESCRIPTION: A 58 years old Indonesian man experienced gross hematuria for 3 months, and thus finally brought to the Emergency Room (ER) where he was initiated urinary catheter and given intravenous (IV) fluid along with analgesic parenterally. Emergency abdominal radiograph assessment and blood test were made. Abdominal radiograph assessment suggests a 6 x 6 cm opacity in the bladder and several urolithiasis in the pelvic cavity. Ureum and creatinine increased in the blood test procedure. Based on the characteristic appearance and radiological findings, a diagnosis of vesicolithiasis was made. Following the diagnosis, the patient was urgently operated on (Open vesicolithotomy), and during the stone removal, there was a tangled polyp-like mass found buried underneath the stone. Histological findings of mass and surrounding lymph nodes were made and histopathologically stated the mass was sarcomatoid carcinoma of the bladder and it had metastated to lymph node and pelvic region. CONCLUSION: Considering hematuria in urolithiasis is frequent, the clinician should be aware of any tumor findings especially when the hematuria is massive thus emergency urolithotomy should be considered immediately.